2013
DOI: 10.1177/0734242x13497079
|View full text |Cite
|
Sign up to set email alerts
|

The influence of earthworms on nutrient dynamics during the process of vermicomposting

Abstract: In the present study the potential of the earthworm Eisenia andrei to modify chemical and microbiological properties, with a special focus on the nutrient content of fresh organic matter, was evaluated during 16 weeks of vermicomposting of cattle manure and sewage sludge. Samples were periodically collected in order to determine the changes in inorganic nitrogen (N), in total microbial biomass and activity, as well as in the total and available content of macro- and micronutrients. An optimal moisture level, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 38 publications
2
22
0
3
Order By: Relevance
“…It is hypothesized that fungal and microalgal hyphae, which easily colonize on freshly deposited worm casts, are contributing to trace level of magnesium in the final vermicompost (Suthar 2010b;Lim et al 2012). Domínguez and Gómez-Brandón (2013) found that the presence of earthworms increased total magnesium content in the solid wastes over time but this effect was more obvious in the manure rather than sewage sludge. Also, Lim et al (2014) found that the final vermicomposts which were derived from palm oil mill effluent after 6 weeks of vermicomposting had higher total magnesium contents when rice straw (rather than soil) was used as an amendment.…”
Section: Nutrient Quality Of the Vermicompostmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that fungal and microalgal hyphae, which easily colonize on freshly deposited worm casts, are contributing to trace level of magnesium in the final vermicompost (Suthar 2010b;Lim et al 2012). Domínguez and Gómez-Brandón (2013) found that the presence of earthworms increased total magnesium content in the solid wastes over time but this effect was more obvious in the manure rather than sewage sludge. Also, Lim et al (2014) found that the final vermicomposts which were derived from palm oil mill effluent after 6 weeks of vermicomposting had higher total magnesium contents when rice straw (rather than soil) was used as an amendment.…”
Section: Nutrient Quality Of the Vermicompostmentioning
confidence: 99%
“…Figure 7 shows that the maximum increases in total magnesium content in the final vermicomposts were obtained from the treatments of E2:D1 (?370.93 %), followed by E3:D1 (?245.36 %), E1:D2 (?206.10 %), E1:D3 (?163.60 %), E1:D1 (?83.58 %) and E (?55.86 %). Some recent studies also indicated that the final vermicomposts contained higher total magnesium content after the earthworms were incorporated into biodegradation process of solid wastes (Domínguez and Gómez-Brandón 2013;Lim et al 2014). Until now, the direct contribution of earthworm in magnesium metabolism is still unclear.…”
Section: Nutrient Quality Of the Vermicompostmentioning
confidence: 99%
“…Ortalama değerler dikkate alındığında ise vermikompostlamanın tütün atığının CO 2 -oluşumunu arttırdığı, TA+AG vermikompostu üzerine ise herhangi bir etkisinin olmadığı anlaşılmaktadır. Dominguez and Gomez-Brandon (2013) yaptıkları çalışmada arıtma çamuru ve ahır gübresinde ortaya çıkan CO 2 -oluşumu üzerine vermikompostlamanın bir etkisinin olmadığını saptarlarken, Pramanik et al, (2009) sığır gübresi ve çim atıklarından yapılan vermikompostalama sonucu mikrobiyal solunumun arttığını belirlemişlerdir.…”
Section: Co 2 -Oluşumuunclassified
“…Vermicomposting, the transformation of organic waste into vermicompost, is a biooxidative mesophilic process in which detritivorous earthworm species interact with microorganisms, strongly affecting decomposition processes, accelerating the stabilization of organic matter, and greatly modifying its physical, chemical, and biological properties [1][2][3][4]. Vermicomposting and vermiculture are well established worldwide and are important for economic and environmental reasons [5].…”
Section: Introductionmentioning
confidence: 99%